An Optimisation Tool for Hybrid-Electric Aircraft Propulsion Systems - Walmsley, Robert; Ahmed, Rishad; Klumpner, Christian; Saleh, Beeond M. (2023 IEEE International Electric Machines & Drives Conference (IEMDC), 2023)
The requirement for reductions in CO 2 , NO X and noise emissions from aviation have come under great assiduity. The use of electric and hybrid-electric propulsion systems within aircraft offer potential performance and efficiency improvements, through reduced fuel consumption, reduced emissions, and reduction in noise. This work proposes a novel multidisciplinary simulation tool, capable of determining optimised propulsion system parameters for various measures of merit (MoM), based on preliminary or conceptual aircraft specifications. Overall power, control and drive system which is to be used within the propulsion systems of hybrid and / or all electric aircraft applications can be determined from the simulation tool. Using an initial sizing algorithm to consider aircraft with hybrid-electric propulsion systems, taking power-to-weight ratio (P/W), wing loading (W/S), and hybridisation of power, as inputs to a mission analysis, and performing an optimisation study to determine a MoM, it has been possible to expand on work in this field with the addition of a supplementary branch in the sizing methodology to include a sizing analysis for the components of an aircraft's electric propulsion system. The designed program enables accurate sizing of powertrain, optimises overall masses, and allows rapid sizing with minimal computational expense.